2020
DOI: 10.1002/ps.5761
|View full text |Cite
|
Sign up to set email alerts
|

NPC1b as a novel target in controlling the cotton bollworm, Helicoverpa armigera

Abstract: BACKGROUND: Insects cannot synthesize sterols and must acquire them from food. The mechanisms underlying how insects uptake dietary sterols are largely unknown except that NPC1b, an integral membrane protein, has been shown to be responsible for dietary cholesterol uptake in Drosophila melanogaster. However, whether NPC1b orthologs in other insect species, particularly the economically important pests, function similarly remains to be determined. RESULTS:In this study, we characterized the function of NPC1b in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…SgNPC1b shows a midgut and associated caeca specific expression ( Figure 5A ), similar to SgVAHa1 , implying a specialized function of SgNPC1b in the midgut, which is consistent with findings in the holometabolan species, D. melanogaster , H. armigera, T. castaneum and Tenebrio molitor ( Voght et al, 2007 ; Oppert et al, 2018 ; Zheng et al, 2020 ). In line with these reports, we found two NPC1-like sequences in T. castaneum in the BeetleAtlas 9 database ( Naseem et al, 2023 ), one putative NPC1a sequence (TC005088) with uniform distribution and one putative NPC1b sequence (TC033918) with midgut-specific expression.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…SgNPC1b shows a midgut and associated caeca specific expression ( Figure 5A ), similar to SgVAHa1 , implying a specialized function of SgNPC1b in the midgut, which is consistent with findings in the holometabolan species, D. melanogaster , H. armigera, T. castaneum and Tenebrio molitor ( Voght et al, 2007 ; Oppert et al, 2018 ; Zheng et al, 2020 ). In line with these reports, we found two NPC1-like sequences in T. castaneum in the BeetleAtlas 9 database ( Naseem et al, 2023 ), one putative NPC1a sequence (TC005088) with uniform distribution and one putative NPC1b sequence (TC033918) with midgut-specific expression.…”
Section: Discussionsupporting
confidence: 86%
“…Due to gene duplication, the majority of insects possess two NPC1 homologues, namely, NPC1a and NPC1b ( Zheng et al, 2018 ). NPC1b was shown to be crucial for dietary sterol absorption in the midgut of D. melanogaster and H. armigera ( Voght et al, 2007 ; Zheng et al, 2020 ). After absorption, sterols are taken up in the lysosomes and are transferred by NPC2 to NPC1a which is integrated in the lysosomal membrane ( Jing and Behmer, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that cholesterol feeding did induce the expression of BtNPC1, supporting its role in sterol absorption. Similarly, in Helicoverpa armigera, the expression of NPC1b was induced after diet injection or cholesterol uptake (Zheng et al, 2020). To date, it seems excessive cholesterol may have adverse effect on BtNPC1…”
Section: Discussionmentioning
confidence: 99%
“…Thus, NPC1b can be a potential target for pest management. However, the technique might have some off-target effects [72]. Wang et al used the CRISPR/Cas9 system in H. armigera and proved that Cry1Ac resistance relies on HaCad (which is also a key receptor of Cry1Ac).…”
Section: Helicoverpa Armigeramentioning
confidence: 99%